Dynamic capabilities, operational capabilities (educational-marketing) and performance - Roseli Wünsch Takahashi, Adriana (2017)
Purpose – To verify the relationship between dynamic capabilities(DCs) and their impact on performance mediated by operationalcapabilities, considering educational technological capabilities andmarketing capabilities in private higher education institutions (HEIs)in Brazil.Design/methodology/approach – A survey was carried out in 1.932higher education institutions, resulting in 316 valid insertions. Researchinvolved dynamic capabilities, operational capabilities, performanceand environmental dynamism constructs.Findings – The research revealed the emergence and explanationof a competitor model containing relationships that had not beenconsidered by previous models, i.e., the direct influence of technologicaleducational capabilities on marketing capabilities.Originality/value – The results revealed greater managerial complexitywhen referring to the relationship between DCs and performance,and contribute to research concerning HEIs in Brazil and to academicmanagement itself.